Making Mongol history : Rashid al-Din and the Jamiʻ al-tawarikh - Kamola, Stefan T. (Edinburgh : Edinburgh University Press, 2019)
"This book examines the life and work of Rashid al-Din Tabib (d. 1318), the most powerful statesman working for the Mongol Ilkhans in the Middle East. It begins with an overview of administrative history and historiography in the early Ilkhanate, culminating with Rashid al-Din's Blessed History of Ghazan, the indispensable source for Mongol and Ilkhanid history. Later chapters lay out the results of the most comprehensive study to date of the manuscripts of Rashid al-Din's historical writing. The complicated relationship between Rashid al-Din's historical and theological writings is also explored, as well as his appropriation of the work of his contemporary historian, 'Abd Allah Qashani."--Publisher
Mongols in a Muslim world, 1218-1280 -- The likely course of an unlikely life, 1248-1302 -- Mongol dynastic history, 1302-1304 -- New projects of faith and power, 1304-1312 -- Remaking Mongol history, 1307-1313 -- Creating the image of Rashid al-Din, 1312-1335 -- Epilogue : Rashid al-Din at the court of Shahrokh.
Includes bibliographical references (pages 272-304) and index.
Print version record.
JSTOR
Keywords: Rashīd al-Dīn Ṭabīb, -- 1247?-1318.; Rashīd al-Dīn Ṭabīb, -- 1247?-1318.; Ilkhanid dynasty; Ilkhanid dynasty; Rashīd al-Dīn Ṭabīb, -- 1247?-1318; Jāmīʻ al-tavārīkh (Rashīd al-Dīn Ṭabīb); Mongols -- History; Mongols -- Histoire; HISTORY -- Historiography; Mongols; Electronic books; History